(untitled) (Vietnam Journal of Community Medicine, 2024)
Objectives: Describes the treatment effectiveness and satisfaction of acne patients who come for examination and treatment at the FOB dermatology clinic using the combined CO2 laser procedure. Materials and Method: A cross-sectional descriptive study was conducted on 72 acne patients examined at the FOB dermatology clinic from May 2022 to July 2023. Results: There was general clinical improvement after 12 weeks of treatment: good (69.4%), good (26.4%), moderate (7.6%), and average (4.2%); average change in GAGS score over time before treatment (31.65); after 12 weeks of treatment (17,76). 91.7% of patients were satisfied with the treatment results. The majority of patients were satisfied with the timing (91.7%), effectiveness (90.3%), and overall performance (90.3%) of the CO2 combination procedure. 88.9% of patients decided to use the method again. Conclusion: The CO2 laser brings high treatment efficiency and patient satisfaction.